2006
DOI: 10.1007/s10933-005-3241-3
|View full text |Cite
|
Sign up to set email alerts
|

Diatom Paleolimnological Record of Holocene Climatic and Environmental Change in the Altai Mountains, Siberia

Abstract: Westover, Karlyn S.; Fritz, Sherilyn C.; Blyakharchuk, Tatyana A.; and Wright, Herbert E., "Diatom paleolimnological record of Holocene climatic and environmental change in the Altai Mountains, Siberia" (2006).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 52 publications
1
13
0
1
Order By: Relevance
“…Temperature was previously found to affect Arctic diatom communities (Hobbs et al 2010;Laing et al 1999). A few studies report slight shifts in the distribution of diatoms with changes in climate over different time scales, but also reveal the continuous presence of Staurosira and Staurosirella over long periods (Biskaborn et al 2012;Westover et al 2006). The distribution of Staurosira and Staurosirella haplotypes in our study might be driven by some of these environmental factors, but further investigations into these factors are needed, as is broader geographic sampling, to address this question.…”
Section: Usability Of Sedimentary Dna For Diatom Identification In Pamentioning
confidence: 64%
“…Temperature was previously found to affect Arctic diatom communities (Hobbs et al 2010;Laing et al 1999). A few studies report slight shifts in the distribution of diatoms with changes in climate over different time scales, but also reveal the continuous presence of Staurosira and Staurosirella over long periods (Biskaborn et al 2012;Westover et al 2006). The distribution of Staurosira and Staurosirella haplotypes in our study might be driven by some of these environmental factors, but further investigations into these factors are needed, as is broader geographic sampling, to address this question.…”
Section: Usability Of Sedimentary Dna For Diatom Identification In Pamentioning
confidence: 64%
“…6f) show the humidity/ precipitation pattern, which makes it similar to the ER before 6 kyr BP and to the WR after that. Ilyashuk and Ilyashuk (2007), using chironomid and lithology records and results of the diatom analysis (Westover et al, 2006), suggested that the Pacific monsoon brought precipitation to the Russian Altai in the early Holocene, whereas cyclones associated with the Atlantic westerlies were likely responsible for the moisture transport during the second half of the Holocene. The reconstructed mid-Holocene phase of relatively dry climatic conditions falls in an interval when a major transformation of the atmospheric circulation occurred in Eurasia.…”
mentioning
confidence: 99%
“…North of the Mongolian Altai, a cold and dry climate in the Early Holocene was reconstructed for the Russian Altai and Tuva (Blyakharchuk et al, 2004(Blyakharchuk et al, , 2007(Blyakharchuk et al, , 2008Westover et al, 2006;Ilyashuk B., Ilyashuk E., 2007). In the southeastern portion of the Mongolian Altai and in Tuva, alpine meadow area coverage decreased, while wormwood steppe with ephedra in combination with yernik tundra expanded.…”
Section: Discussionmentioning
confidence: 99%
“…Several publications are focused on the Late Pleistocene and Holocene environmental changes in Northern and Central Kazakhstan (Tarasov, Jolly, Kaplan, 1997;Kremenetski, Tarasov, Cherkinsky, 1997), and in the Russian Altai and Tuva (Blyakharchuk et al, 2004(Blyakharchuk et al, , 2007(Blyakharchuk et al, , 2008Schlütz, Lehmkuhl, 2007). These works are supplemented by results of analysis of diatom (Westover et al, 2006) and chironomid remains (Ilyashuk B., Ilyashuk E., 2007) from the Altai and Tuva.…”
Section: Based On Palynological and Diatom Analyses Of The Sediment Cmentioning
confidence: 99%